Economic regulation of privatised airports: Some lessons from UK experience. (August 2018) - Littlechild, Stephen
Highlights: Restructuring airport sectors is more difficult after privatisation than before. Airport regulation will and should evolve over time. As competition develops, airport regulation can be reduced. Reduced regulation involves more negotiation between airports, airlines and their customers. Abstract: This paper describes the evolution over time of policy, structure, competition and regulation of UK airports. Restructuring an airport sector at the time of privatisation will better enable airports to compete. If this is not done, the structure can be revised later, although by then the opposition will be greater. The appropriate form and focus of airport regulation will and should evolve over time, as experience accumulates and as economic and technical opportunities themselves evolve. As competition develops, the extent of airport regulation can with advantage be reduced over time, with a correspondingly increased role for airlines and their customers.